Detection Of Sm Gene Resistance To Gray Leaf Spot In (Stemphylium Spp.) Tomato Cultivars Iraq - Al Rufaye, Zeina Thamer Abd ULHussein; AL Sheikh , Warqaa Muhammed Shariff; Ghaleb, Intisar Kadhum (Comunicata Scientiae, 2024)
Abstract Gray leaf spot, Occurs due to Stemphylium spp., is a foliar disease in tomato. The Resistance against gray leaf spot disease is conferred by a single incompletely dominant gene Sm located on chromosome 11. This study aimed to identify cultivar resistant alleles or susceptible alleles by molecular marker tightly linked to the Sm gene and the use of marker-assisted selection inbreeding. In this study, we used eight tomato cultivars Farmed in Iraq. The analysis demonstrated that the co-dominant marker Sm-InDel, which produced 122-bp fragment for resistance in seven genotypes and a 140-bp fragment for susceptible alleles in one genotype, respectively could be utilized in Marker-assisted selection (MAS)for gray leaf spot resistance.